ChemInform Abstract: Convenient and Practical Alkynylation of Heteronucleophiles with Copper Acetylides. Issue 41 (7th October 2014) - Theunissen, Cedric; Lecomte, Morgan; Jouvin, Kevin; Laouiti, Anouar; Guissart, Celine; Heimburger, Jeremy; Loire, Estelle; Evano, Gwilherm
Abstract Copper acetylides, activated by oxidation with oxygen in the presence of simple nitrogen ligands, undergo a formal umpolung and are able to transfer their alkyne subunit to a wide range of heteronucleophiles, including amides, oxazolidinones, imines and dialkyl phosphites.